Preparation method of superfine modified coal gangue powder
Through steps such as quench cooling treatment, rapid heating, acidolysis, alkali neutralization and corona treatment, ultrafine coal gangue powder with a particle size less than 2μm was prepared, which solved the problem of insufficient performance of coal gangue in application, improved its reaction activity and adsorption capacity, and achieved high value-added utilization of resources.
Patent Information
- Application Number
- CN202510083383.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The hardness and brittleness of coal gangue are uneven, the particles are large and irregular in shape, making it difficult to meet the required performance requirements in some applications, and its surface is inert and chemical reactivity is low, limiting its use in applications where high reactivity is required.
By preparing an aqueous isopropanol solution for quenching, combining rapid heating and ball mill grinding, acidolysis and alkali neutralization treatment, and adding modifiers during the corona treatment process, ultrafine coal gangue powder with a particle size less than 2 μm was prepared.
The prepared ultrafine coal gangue powder has a fine particle size and a larger specific surface area, which improves its reactivity and adsorption capacity in various applications, and realizes the transformation from waste to valuable resources.
Smart Images

Figure CN119909649A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of new material manufacturing, and in particular to a method for preparing ultrafine modified coal gangue powder. Background Art
[0002] Gangue is solid waste generated during coal mining and washing, usually containing a certain amount of carbonaceous materials and other minerals. It is estimated that China produces about 600 million tons of gangue each year, accounting for more than one-third of the country's total industrial solid waste. For a long time, these gangues have been simply piled up or landfilled, which not only occupies a large amount of land resources, but also may cause geological disasters such as landslides and mud-rock flows. Moreover, over time, the harmful components in the gangue will gradually seep into the soil and groundwater, causing environmental pollution.
[0003] From another perspective, coal gangue is also a mineral resource that has not been fully utilized. Studies have shown that in addition to a small amount of carbon, coal gangue is also rich in silicon (Si), aluminum (Al), iron (Fe), calcium (Ca) and other elements, especially calcium, which can be used to make various building materials, such as cement, bricks and tiles.
[0004] However, the hardness and brittleness of coal gangue are uneven, and the particles are large and irregular in shape, which makes it difficult to achieve the required performance requirements in some applications. In particular, the agglomeration phenomenon between the original coal gangue particles is serious, and it is not easy to mix evenly with other materials, which reduces its applicability in composite materials or other application scenarios. In addition, the surface of coal gangue is relatively inert and the chemical reactivity is low, which limits its use in application fields that require high reactivity. Summary of the invention
[0005] Purpose of the invention: In view of the shortcomings of the prior art, the present invention proposes a method for preparing ultrafine modified coal gangue powder. The ultrafine coal gangue powder prepared by the method has a suitable particle size and a large specific surface area. It solves many problems caused by the direct application of coal gangue, and also finds a higher value-added application path for it, realizing the transformation from waste to valuable resources.
[0006] Technical solution: The present invention provides a method for preparing ultrafine modified coal gangue powder, and the specific steps are as follows:
[0007] First, prepare an isopropanol aqueous solution for use. The isopropanol solution ratio is: 10g of isopropanol is dissolved in 500ml of water. The isopropanol solution can lower the freezing point of the solution. When the heated coal gangue is quickly poured into the solution, the surface of the coal gangue shrinks rapidly due to the great temperature difference, generating internal stress, so that the coal gangue bursts into smaller particles. This step helps to increase the specific surface area of the coal gangue and provide more active sites for subsequent chemical reactions.
[0008] The large pieces of coal gangue are preliminarily crushed to meet the requirements of subsequent processing equipment. The crushed coal gangue is rapidly heated to 800±20℃. This process needs to be completed in a short time. Through rapid heating, a temperature difference is generated inside and outside the mineral particles, resulting in lattice distortion and stress difference, forming microcracks, especially for mineral components such as quartz, which helps to reduce its binding energy and promote subsequent crushing. For the present invention, the heating rate is greater than 200℃ / min, preferably 250℃ / min. The heated coal gangue is immediately poured into the above-mentioned isopropanol aqueous solution for quenching treatment. Due to the huge temperature difference change, the mineral particles burst instantly. The exploded coal gangue is obtained, divided into two equal parts, one for standby use, and the other for acid hydrolysis, and then neutralized by alkali to obtain a precipitate, which is mixed with the above-mentioned standby coal gangue of equal mass, and loaded into a ball mill for grinding. The coal gangue part treated with acid hydrolysis (acid leaching) will dissolve some unstable mineral phases and release soluble metal ions. These ions form hydroxide precipitates after the addition of NaOH. This chemical treatment can change the composition of the gangue, exposing more active sites, thereby increasing the reactivity in subsequent processing or applications. At the same time, mixing two gangues in different treatment states can help produce a more uniform and finer particle distribution during the ball milling process because the hardness and brittleness of the two may be different. Moreover, the part treated with acid hydrolysis and alkali neutralization may introduce new crystalline or amorphous phases, which, when mixed with the original gangue, can promote the formation of new phases during the grinding process and further optimize the microstructure of the powder.
[0009] After grinding, the ground slurry is subjected to solid-liquid separation for 10 to 20 minutes. After separation, the solid precipitate is dried and then ground and dispersed to obtain a powder with a particle size D50 less than 2 μm. The powder is evenly spread on the rotating disk of the corona treatment machine, the rotation speed is set to 5-15 rpm, the corona discharge voltage is set to 20 kV, and the current density is about 0.1 mA / cm 2 , the nitrogen flow rate is 1L / min, and the corona discharge device is turned on. During this process, high-energy electrons will impact the surface of the coal gangue particles, causing the surface molecular bonds to break, forming free radicals and other active sites, and changing the surface properties of the powder. The treatment time is 3-5 minutes. After the treatment is completed, the coal gangue powder is obtained.
[0010] Specifically, the grinding is performed using zirconia ceramic balls with a diameter of 2 mm as grinding media at a rotation speed of 1500 rpm for 60-90 minutes.
[0011] Specifically, the drying is carried out under vacuum conditions at 95°C.
[0012] Specifically, the rotation speed is preferably set to 10 rpm.
[0013] Specifically, the acid hydrolysis is as follows: adding 6M HCl solution at a solid-liquid ratio of 1:10, stirring at 80° C. for 30 minutes, filtering after the reaction is completed, and collecting the filtrate.
[0014] Specifically, the alkali neutralization is as follows: slowly adding 5% NaOH solution to the filtrate until the pH value reaches 9-10 to obtain a precipitate.
[0015] As a further improvement, the coal gangue after explosion is loaded into a ball mill, a modifier (a n-propanol solution containing 2 wt % KH550) is added, and zirconium oxide ceramic balls (diameter 2 mm) are used as grinding media, and the mill is ground at a speed of 800 rpm for 100-120 minutes.
[0016] As a further improvement, during the corona discharge treatment, a modifier is slowly sprayed into the treatment area through a precision sprayer. The modifier is a n-propanol solution containing 2wt% KH550, and the total liquid volume is 10ml, to ensure that the modifier is evenly covered on the surface of the gangue powder. Adding the modifier during the corona treatment process can improve the compatibility between the gangue powder and the polymer matrix, prevent stratification or peeling caused by temperature changes, and increase the thermal stability of the material. At the same time, through the action of the modifier, the bonding between the gangue powder and the polymer matrix is strengthened, thereby improving the strength, toughness and impact resistance of the hollow board.
[0017] Beneficial effects: The present invention reduces the occurrence of agglomeration during the preparation process by mixing raw materials in different processing states, and can regulate the particle size and morphology of the final powder to a certain extent, thereby obtaining an ultrafine powder with uniform particle size distribution and regular morphology. At the same time, a new crystal form or amorphous phase may be introduced, thereby optimizing the microstructure of the powder and activating the minerals in the gangue to expose more active sites, thereby improving the reaction activity of the final product and facilitating subsequent applications.
[0018] The ultrafine coal gangue powder obtained by the method of the present invention has a finer particle size and a larger specific surface area, which not only increases the chance of contact with external substances, but also enhances its reactivity and adsorption capacity in various applications. The particle size distribution of the present invention is very ideal for many applications, for example, it can provide a higher packing density and better mechanical properties when used as a filling material.
[0019] The preparation method provided by the present invention fully utilizes the industrial waste of coal gangue and converts it into high value-added ultrafine powder material, thereby realizing the recycling of waste and helping to reduce the environmental burden. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The sample prepared in Example 1 is shown.
[0021] Figure 2 This is the SEM image of the sample prepared in Example 1.
[0022] Figure 3 This is the SEM electron microscope image of the coal gangue raw material processed in Example 1. DETAILED DESCRIPTION
[0023] The technical solution of the present application is described in detail below through embodiments, but the protection scope of the present application is not limited to the embodiments.
[0024] Example 1
[0025] Prepare isopropanol aqueous solution (ratio: 10g isopropanol: 500ml water) for standby. Preliminary crushing of bulky coal gangue, rapid heating of crushed coal gangue to about 800°C, heating rate of 250°C / min, pouring heated coal gangue into the above solution immediately for quenching, obtaining coal gangue after explosion, dividing it into two parts of equal mass, one for standby, and adding 6M HCl solution to the other according to the ratio of solid-liquid ratio of 1:10, stirring for 30 minutes at 80°C, after completing the reaction, filtering, slowly adding 5% NaOH solution to the filtrate until the pH value reaches 9-10, obtaining precipitate, mixing this precipitate with the above-mentioned standby equal mass coal gangue, loading into ball mill together, grinding at a speed of 1500rpm for 60-90 minutes with zirconium oxide ceramic balls (diameter 2mm) as grinding media.
[0026] After grinding, a centrifuge is used to separate the solid and liquid of the ground slurry for about 10 to 20 minutes. The separated liquid can be returned to the production process for recycling. The solid precipitate is dried under low temperature (95°C) vacuum conditions and then ground and dispersed to obtain a powder with a particle size D50 less than 2μm.
[0027] The above powder was evenly spread on the rotating disk of the corona treater, the rotation speed was set to 10 rpm, the corona discharge voltage was set to 20 kV, and the current density was about 0.1 mA / cm 2 , nitrogen flow rate is 1L / min, corona discharge device is turned on, treatment time is 3 minutes, after treatment, coal gangue powder is obtained. Collect samples such as Figure 1 The SEM electron microscope image of the obtained coal gangue powder is shown as follows Figure 2 The SEM electron microscope image of the coal gangue raw material is shown in Figure 3 As shown. Figure 2 and Figure 3 It can be seen from the comparison that the surface microstructure of the coal gangue raw material before treatment and the ultrafine coal gangue powder after treatment are obviously different.
[0028] Example 2
[0029] Prepare isopropanol aqueous solution (ratio: 10g isopropanol: 500ml water) for standby. Preliminary crushing of bulky coal gangue, rapid heating of crushed coal gangue to about 800°C, heating rate of 50°C / min, pouring heated coal gangue into the above solution immediately for quenching treatment, obtaining coal gangue after explosion, dividing it into two parts of equal mass, one for standby, and adding 6M HCl solution to the other according to the ratio of solid-liquid ratio of 1:10, stirring at 80°C for 30 minutes, after completing the reaction, filtering, slowly adding 5% NaOH solution to the filtrate until the pH value reaches 9-10, obtaining precipitate, mixing this precipitate with the above-mentioned standby equal mass coal gangue, loading into ball mill together, grinding at a speed of 1500rpm for 60-90 minutes with zirconium oxide ceramic balls (diameter 2mm) as grinding media.
[0030] After grinding, a centrifuge is used to separate the solid and liquid of the ground slurry for about 10 to 20 minutes. The separated liquid can be returned to the production process for recycling. The solid precipitate is dried under low temperature (95°C) vacuum conditions and then ground and dispersed to obtain a powder with a particle size D50 less than 2μm.
[0031] The above powder was evenly spread on the rotating disk of the corona treater, the rotation speed was set to 10 rpm, the corona discharge voltage was set to 20 kV, and the current density was about 0.1 mA / cm 2 , the nitrogen flow rate is 1L / min, the corona discharge device is turned on, the treatment time is 3 minutes, and after the treatment is completed, coal gangue powder is obtained.
[0032] Example 3
[0033] The large pieces of coal gangue were preliminarily crushed, and the crushed coal gangue was rapidly heated to about 800°C at a heating rate of 250°C / min. The heated coal gangue was immediately poured into water for quenching to obtain the exploded coal gangue, which was divided into two equal parts, one for standby use, and the other part was added with 6M HCl solution at a solid-liquid ratio of 1:10, and stirred at 80°C for 30 minutes. After the reaction was completed, it was filtered, and 5% NaOH solution was slowly added to the filtrate until the pH value reached 9-10 to obtain a precipitate. The precipitate was mixed with the above-mentioned standby coal gangue of equal mass, and they were loaded into a ball mill together. Zirconia ceramic balls (diameter 2mm) were used as grinding media and ground at a speed of 1500rpm for 60-90 minutes.
[0034] After grinding, a centrifuge is used to separate the solid and liquid of the ground slurry for about 10 to 20 minutes. The separated liquid can be returned to the production process for recycling. The solid precipitate is dried under low temperature (95°C) vacuum conditions and then ground and dispersed to obtain a powder with a particle size D50 less than 2μm.
[0035] The above powder was evenly spread on the rotating disk of the corona treater, the rotation speed was set to 10 rpm, the corona discharge voltage was set to 20 kV, and the current density was about 0.1 mA / cm 2 , the nitrogen flow rate is 1L / min, the corona discharge device is turned on, the treatment time is 3 minutes, and after the treatment is completed, coal gangue powder is obtained.
[0036] Comparative Example 1
[0037] Prepare an isopropanol aqueous solution (ratio: 10g isopropanol: 500ml water) for later use. Preliminary crushing of large pieces of coal gangue, rapid heating of the crushed coal gangue to about 800°C, heating rate of 50°C / min, immediately pouring the heated coal gangue into the above solution for quenching, loading the cracked coal gangue into a ball mill, using zirconium oxide ceramic balls (diameter 2mm) as grinding media, grinding at a speed of 1500rpm for 60-90 minutes.
[0038] After grinding, a centrifuge is used to separate the solid and liquid of the ground slurry for about 10 to 20 minutes. The separated liquid can be returned to the production process for recycling. The solid precipitate is dried under low temperature (95°C) vacuum conditions and then ground and dispersed to obtain a powder with a particle size D50 less than 2μm.
[0039] The above powder was evenly spread on the rotating disk of the corona treater, the rotation speed was set to 10 rpm, the corona discharge voltage was set to 20 kV, and the current density was about 0.1 mA / cm 2 , the nitrogen flow rate is 1L / min, the corona discharge device is turned on, the treatment time is 3 minutes, and after the treatment is completed, coal gangue powder is obtained.
[0040] Comparative Example 2
[0041] The large pieces of coal gangue were preliminarily crushed, and the crushed coal gangue was divided into two equal parts, one of which was reserved, and the other was added with 6M HCl solution at a solid-liquid ratio of 1:10, and stirred at 80°C for 30 minutes. After the reaction was completed, it was filtered, and 5% NaOH solution was slowly added to the filtrate until the pH value reached 9-10 to obtain a precipitate. The precipitate was mixed with the above-mentioned reserved coal gangue of equal mass, and they were loaded into a ball mill together, and zirconia ceramic balls (diameter 2mm) were used as grinding media, and the mixture was ground at a speed of 1500rpm for 60-90 minutes.
[0042] After grinding, a centrifuge is used to separate the solid and liquid of the ground slurry for about 10 to 20 minutes. The separated liquid can be returned to the production process for recycling. The solid precipitate is dried under low temperature (95°C) vacuum conditions and then ground and dispersed to obtain a powder with a particle size D50 less than 2μm.
[0043] The above powder was evenly spread on the rotating disk of the corona treater, the rotation speed was set to 10 rpm, the corona discharge voltage was set to 20 kV, and the current density was about 0.1 mA / cm 2 , the nitrogen flow rate is 1L / min, the corona discharge device is turned on, the treatment time is 3 minutes, and after the treatment is completed, coal gangue powder is obtained.
[0044] Comparative Example 3
[0045] Prepare isopropanol aqueous solution (ratio: 10g isopropanol: 500ml water) for standby. Preliminary crushing of bulky coal gangue, rapid heating of crushed coal gangue to about 800°C, heating rate of 250°C / min, pouring heated coal gangue into the above solution immediately for quenching, obtaining coal gangue after explosion, dividing it into two parts of equal mass, one for standby, and adding 6M HCl solution to the other according to the ratio of solid-liquid ratio of 1:10, stirring for 30 minutes at 80°C, after completing the reaction, filtering, slowly adding 5% NaOH solution to the filtrate until the pH value reaches 9-10, obtaining precipitate, mixing this precipitate with the above-mentioned standby equal mass coal gangue, loading into ball mill together, grinding at a speed of 1500rpm for 60-90 minutes with zirconium oxide ceramic balls (diameter 2mm) as grinding media.
[0046] The ground slurry is separated into solid and liquid using a centrifuge for about 10 to 20 minutes. The separated liquid can be returned to the production process for recycling. The solid precipitate is dried under low temperature (95°C) vacuum conditions and then ground and dispersed to obtain coal gangue powder.
[0047] The test data of the coal gangue powder prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are as follows:
[0048]
[0049] Comparative Example 1 did not divide it into two halves and then mix them after treatment; Comparative Example 2 did not adopt the rapid heating and cooling treatment method, and Comparative Example 3 did not adopt corona treatment in the subsequent stage. Through the comparison of the above data, it can be seen that the coal gangue powder obtained by the treatment method adopted in Example 1 has a finer particle size, a larger specific surface area, a larger porosity, and a suitable particle size and an ideal pore structure.
[0050] Application test 1
[0051] The coal gangue powder obtained in Example 1 was used to produce stone paper. The obtained stone paper had a stiffness of 0.5 mN·m, a tensile strength of 51 MPa, and a tear strength of 150 mN·m. 2 / g.
[0052] The coal gangue powder obtained in Example 1 was used to manufacture a hollow board. The obtained hollow board had a tensile strength of 25.1 MPa, a flexural strength of 34.1 MPa, a heat deformation temperature of 112°C, and a Vicat softening point of 145°C.
[0053] Application Test 2
[0054] The coal gangue powder obtained in Comparative Example 1 was used to make stone paper. The obtained stone paper had a stiffness of 0.5 mN·m, a tensile strength of 43 MPa, and a tear strength of 125 mN·m. 2 / g.
[0055] The coal gangue powder obtained in Comparative Example 1 was used to manufacture a hollow board. The obtained hollow board had a tensile strength of 20.8 MPa, a bending strength of 30.5 MPa, a heat deformation temperature of 112°C, and a Vicat softening point of 145°C.
[0056] Application test 3
[0057] The coal gangue powder obtained in Comparative Example 2 was used to make stone paper. The obtained stone paper had a stiffness of 0.5 mN·m, a tensile strength of 48 MPa, and a tear strength of 134 mN·m. 2 / g.
[0058] The coal gangue powder obtained in Comparative Example 2 was used to manufacture a hollow board. The obtained hollow board had a tensile strength of 21.2 MPa, a flexural strength of 29.8 MPa, a heat deformation temperature of 112°C, and a Vicat softening point of 145°C.
[0059] Application test 4
[0060] The coal gangue powder obtained in Comparative Example 3 was used to make stone paper. The obtained stone paper had a stiffness of 0.5 mN·m, a tensile strength of 44 MPa, and a tear strength of 132 mN·m. 2 / g.
[0061] The coal gangue powder obtained in Comparative Example 3 was used to manufacture a hollow board. The obtained hollow board had a tensile strength of 18.9 MPa, a flexural strength of 21.9 MPa, a heat deformation temperature of 110°C, and a Vicat softening point of 142°C.
[0062] Through the above experiments, it can be seen that the stone paper and hollow board prepared with the gangue powder obtained in the embodiment as raw material are better than the products prepared with the gangue powder obtained in comparative examples 1 to 3 as raw material. The performance of the product obtained in comparative example 3 is obviously lower, which shows that the corona treatment has a greater impact on the performance of subsequent products.
[0063] Example 6
[0064] Prepare an isopropanol aqueous solution (ratio: 10g isopropanol: 500ml water) for standby use. Preliminary crushing of large pieces of coal gangue, rapid heating of the crushed coal gangue to about 800°C, heating rate of 250°C / min, immediately pouring the heated coal gangue into the above solution for quenching, loading the cracked coal gangue into a ball mill, adding a modifier (n-propanol solution containing 2wt% KH550), using zirconium oxide ceramic balls (diameter 2mm) as grinding media, grinding at a speed of 800rpm for 100-120 minutes to achieve organic modification of the surface of the mineral particles, improve its dispersibility and compatibility with other materials.
[0065] After grinding, a centrifuge is used to separate the solid and liquid of the ground slurry for about 10 to 20 minutes. The separated liquid can be returned to the production process for recycling. The solid precipitate is dried under low temperature (95°C) vacuum conditions and then ground and dispersed to obtain a powder with a particle size D50 less than 2μm.
[0066] The above powder was evenly spread on the rotating disk of the corona treater, the rotation speed was set to 10 rpm, the corona discharge voltage was set to 20 kV, and the current density was about 0.1 mA / cm 2 , the nitrogen flow rate is 1 L / min, the corona discharge device is turned on, and the treatment time is 3 minutes. After the treatment is completed, the coal gangue powder of the present invention is obtained.
[0067] Example 7
[0068] Prepare an isopropanol aqueous solution (ratio: 10g isopropanol: 500ml water) for later use. Preliminary crushing of large pieces of coal gangue, rapid heating of the crushed coal gangue to about 800°C, heating rate of 250°C / min, immediately pouring the heated coal gangue into the above solution for quenching, loading the cracked coal gangue into a ball mill, using zirconium oxide ceramic balls (diameter 2mm) as grinding media, grinding at a speed of 1500rpm for 60-90 minutes.
[0069] After grinding, a centrifuge is used to separate the solid and liquid of the ground slurry for about 10 to 20 minutes. The separated liquid can be returned to the production process for recycling. The solid precipitate is dried under low temperature (95°C) vacuum conditions and then ground and dispersed to obtain a powder with a particle size D50 less than 2μm.
[0070] The above powder was evenly spread on the rotating disk of the corona treater, the rotation speed was set to 10 rpm, the corona discharge voltage was set to 20 kV, and the current density was about 0.1 mA / cm 2, the nitrogen flow rate is 1L / min, the corona discharge device is turned on, and the treatment time is 3 minutes. While the corona discharge treatment is in progress, the modifier (a n-propanol solution containing 2wt% KH550) is slowly sprayed into the treatment area through a precision sprayer, with a total liquid volume of 10ml, to ensure that the modifier is evenly covered on the surface of the coal gangue powder. Since the modifier used in this case is an organic solvent soluble type, no additional cleaning step is required. After the treatment, the coal gangue powder of the present invention is obtained.
[0071] Application Test 5
[0072] The coal gangue powder obtained in Example 6 was used to produce stone paper. The obtained stone paper had a stiffness of 0.5 mN·m, a tensile strength of less than 50 MPa, and a tear strength of 151 mN·m. 2 / g.
[0073] The coal gangue powder obtained in Example 6 was used to manufacture a hollow board. The obtained hollow board had a tensile strength of 35.1 MPa, a flexural strength of 35.1 MPa, a heat deformation temperature of 130°C, and a Vicat softening point of 160°C.
[0074] Application test 6
[0075] The coal gangue powder obtained in Example 7 was used to produce stone paper. The obtained stone paper had a stiffness of 0.5 mN·m, a tensile strength of 49 MPa, and a tear strength of 148 mN·m. 2 / g.
[0076] The coal gangue powder obtained in Example 1 was used to manufacture a hollow board. The obtained hollow board had a tensile strength of 39.6 MPa, a flexural strength of 35.9 MPa, a heat deformation temperature of 135°C, and a Vicat softening point of 164°C.
[0077] By comparing application tests 5 and 6 with the previous application tests, it can be seen that for the preparation of stone paper, adding additives in the preparation process of coal gangue powder has little effect and does not improve the product performance. However, for hollow boards, it can effectively improve their thermal stability, especially when added during the corona treatment process, which can not only improve its mechanical properties but also significantly improve the thermal stability of the product.
Claims
1. A method for preparing ultrafine modified coal gangue powder, characterized in that: Prepare an isopropanol aqueous solution for standby use; preliminarily crush large pieces of coal gangue, rapidly heat the crushed coal gangue to 800±20°C, with a heating rate greater than 200°C / min, immediately pour the heated coal gangue into the isopropanol aqueous solution for quenching to obtain cracked coal gangue, divide it into two equal parts, one for standby use, and the other for acid hydrolysis, then neutralize with alkali to obtain a precipitate, mix the precipitate with the above-mentioned standby coal gangue of equal mass, and put them into a ball mill for grinding. After grinding, perform solid-liquid separation on the ground slurry for 10 to 20 minutes, dry the solid precipitate after separation, and then grind and disperse it to obtain a powder with a particle size D50 less than 2μm; evenly spread the powder on a rotating disk of a corona treatment machine, set the rotation speed to 5-15rpm, set the corona discharge voltage to 20kV, and set the current density to about 0.1mA / cm 2 , the nitrogen flow rate is 1L / min, the corona discharge device is turned on, the treatment time is 3-5 minutes, and after the treatment is completed, the coal gangue powder is obtained.
2. The method for preparing ultrafine modified coal gangue powder according to claim 1, characterized in that: The isopropanol solution is prepared in the following proportions: 10 g of isopropanol is dissolved in 500 ml of water.
3. The method for preparing ultrafine modified coal gangue powder according to claim 1, characterized in that: The heating rate is 250°C / min.
4. The method for preparing ultrafine modified coal gangue powder according to claim 1, characterized in that: The grinding is carried out using zirconia ceramic balls with a diameter of 2 mm as grinding media at a rotation speed of 1500 rpm for 60-90 minutes.
5. The method for preparing ultrafine modified coal gangue powder according to claim 1, characterized in that: The drying is carried out under vacuum conditions at 95°C.
6. The method for preparing ultrafine modified coal gangue powder according to claim 1, characterized in that: The acid hydrolysis is specifically as follows: adding 6M HCl solution at a solid-liquid ratio of 1:10, stirring at 80° C. for 30 minutes, filtering after the reaction is completed, and collecting the filtrate.
7. The method for preparing ultrafine modified coal gangue powder according to claim 1, characterized in that: The neutralization by alkali is as follows: slowly adding 5% NaOH solution to the filtrate until the pH value reaches 9-10 to obtain a precipitate.
8. The method for preparing ultrafine modified coal gangue powder according to claim 1, characterized in that: The rotation speed was set to 10 rpm.
9. The method for preparing ultrafine modified coal gangue powder according to claim 1, characterized in that: A modifier is added during the ball milling process, wherein the modifier is a n-propanol solution containing 2 wt % KH550.
10. The method for preparing ultrafine modified coal gangue powder according to claim 1, characterized in that: While the corona discharge treatment is being carried out, a modifier is slowly sprayed into the treatment area through a precision sprayer. The modifier is a n-propanol solution containing 2 wt % KH550.
Citation Information
Patent Citations
Rubber reinforcing filler and method for preparing the same by activating and modifying coal gangue
CN113956682A
Method for selecting valuable minerals in coal gangue
CN114247554A
Preparation method of anti-shrinkage all-solid waste alkali-activated cementing material
CN117430358A
Method for preparing, using coal gangue, composite pigment filler for coating
WO2022233038A1